2016
DOI: 10.1016/j.jagp.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

PTSD and Risk of Incident Cardiovascular Disease in Aging Veterans

Abstract: Findings highlight the longitudinal impact of PTSD on increasing the incidence of cardiovascular disease in older adults. This study implies the need for greater monitoring and treatment of PTSD in older persons, particularly older veterans, to assist in preventing adverse outcomes, such as cardiovascular disease, over the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 37 publications
(26 reference statements)
4
70
0
3
Order By: Relevance
“…Resilience is the capacity for and process of successful overcoming traumatic stress. Given a high prevalence of CVD in patients with PTSD, there is an urgent need for a more active monitoring, treatment (Beristianos et al 2016), increasing resilience and multidisciplinary management , Rosenbaum et al 2015 of PTSD patients, particularly war veterans. Potential biomarkers, as well as some personality and behavioral characteristics, may be useful for assessing both the CVD risks and the utility of potential interventions and resilience training.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resilience is the capacity for and process of successful overcoming traumatic stress. Given a high prevalence of CVD in patients with PTSD, there is an urgent need for a more active monitoring, treatment (Beristianos et al 2016), increasing resilience and multidisciplinary management , Rosenbaum et al 2015 of PTSD patients, particularly war veterans. Potential biomarkers, as well as some personality and behavioral characteristics, may be useful for assessing both the CVD risks and the utility of potential interventions and resilience training.…”
Section: Resultsmentioning
confidence: 99%
“…American war veterans with PTSD, 55 years and older, had increased risk for CVD generally, and in particular myocardial infarction, and peripheral vascular disease as well as congestive heart failure, compared to veterans without PTSD (Beristianos et al 2016). Similarly, in a sample of 501 Croatian war veterans suffering from PTSD, aged between 36 and 65 years, the incidence of arterial hypertension, cardiac arrhythmias and myocardial infarction was significantly higher compared to a healthy control group (Britvi et al 2015).…”
Section: Posttraumatic Stress Disorder: Emerging Risk Factors For Carmentioning
confidence: 98%
“…Although investigators have examined posttraumatic stress disorder in relation to a range of health outcomes (including rheumatoid arthritis, stroke, heart disease, and cancer), some of the strongest empirical research, in terms of methodology and findings, has been with cardiometabolic diseases. 70,71 Numerous methodologically rigorous prospective population-based observational studies have found that posttraumatic stress disorder is associated with increased risk of incident CVD [72][73][74][75][76][77][78][79][80][81][82][83][84] and T2DM. [85][86][87] However, whether and how much of the relation between childhood adversity and cardiometabolic disease may be explained by posttraumatic stress disorder is unclear, especially because these studies have included traumatic events over the life course, with a substantial proportion of studies focused on veterans and military service-related trauma, not just adversity during childhood.…”
Section: Mental Health Factorsmentioning
confidence: 99%
“…While investigators have examined PTSD in relation to a range of health outcomes (including rheumatoid arthritis, stroke, heart disease, and cancer), some of the strongest empirical research—in terms of methodology and findings—has been with cardiometabolic diseases (Lohr et al , 2015). Numerous methodologically rigorous prospective population-based observational studies have found PTSD is associated with increased risk of incident cardiovascular disease (CVD) (Beristianos et al , 2014, Boscarino, 2006, 2008, Boscarino and Chang, 1999, Chen et al , 2015, Gradus et al , 2015, Jordan et al , 2011, Kubzansky et al , 2009, Kubzansky et al , 2007, Roy et al , 2015, Scherrer et al , 2010, Sumner et al , 2015, Vaccarino et al , 2013) and type 2 diabetes (T2D) (Boyko et al , 2010, Roberts et al , 2015, Vaccarino et al , 2014), even after adjusting for depression (see Table 1). …”
Section: Introductionmentioning
confidence: 99%